Corpo, saúde e beleza em aulas de Educação Física no currículo do estado de São Paulo - Dutra, Camila Roldão [UNESP] (Universidade Estadual Paulista (Unesp), 2018)
The concepts of Physical Activity, Exercise and Health have always been present in School Physical Education, but as technical knowledge related to the prescription of exercise and its execution, devaluing some essential aspects. Thus, in order for knowledge to be fully propagated, it is necessary for Physical Education to follow adequate didactic strategies, so that the use of this information is effective so that students can actually achieve long-term behavior changes without restricting themselves only to an addition to their repertoire of health information. As a general objective, the project will evaluate the learning of contents related to the 3rd bimester of the 1st grade of high school among students of state schools in the city of Bauru - São Paulo, referring to the theme Body, health and beauty - Concepts: Physical Activity, Exercise Physical and Health . Then, questionnaires were applied to 2nd and 3rd grade high school students, seeking information about experiences / experiences related to learning the subject, aiming to analyze the achievement of autonomy for the management of basic physical exercise programs. With the teachers, we verified positive and / or negative aspects regarding the development of the subject, especially regarding the initial level of knowledge presented by the students, their motivation during the approach of the theme and the level of learning obtained. The analysis of the collected data of the students and the teachers, on the level of knowledge before and after the approach of the thematic in the classes, comparative way, grouping negative and / or positive aspects. We can observe that there were significant changes in the students' daily life, allowing them greater autonomy to perform physical exercises outside the school environment, based on the information / experiences... (Complete abstract electronic acess below)

Os conceitos de Atividade Física, Exercício e Saúde sempre estiveram presentes na Educação Física escolar, porém como conhecimento técnico relacionado à prescrição de exercício e sua execução, desvalorizando alguns aspectos essências. Assim, para que o conhecimento seja propagado de maneira integral, é necessário que a Educação Física siga estratégias didáticas adequadas, de modo que a utilização dessas informações seja eficaz para que os alunos realmente consigam mudanças de condutas em longo prazo, sem restringir-se apenas a um acréscimo ao seu repertório de informações sobre saúde. Como objetivo geral, está pesquisa avaliará a aprendizagem dos conteúdos referentes ao 3º bimestre da 1ª série do Ensino Médio entre alunos de escolas estaduais no município de Bauru - São Paulo, referente à temática Corpo, saúde e beleza - Conceitos: Atividade Física, Exercício Físico e Saúde. Foram aplicados questionários a alunos da 2ª e 3ª série do Ensino Médio, buscando informações sobre experiências/vivências relativas ao aprendizado da temática, visando analisar a obtenção de autonomia para gerenciamento de programas básicos de exercícios físicos. Com os professores, verificamos aspectos positivos e/ou negativos quanto ao desenvolvimento da temática, especialmente quanto ao nível inicial de conhecimento apresentado pelos alunos, motivação destes durante a abordagem do tema e nível de aprendizado obtido. A análise dos dados coletados do aos alunos e aos professores, sobre o nível de conhecimento pré e pós-abordagem da temática nas aulas, de modo comparativo, agrupando aspectos negativos e/ou positivos. Podemos observar que houve mudanças significativas no cotidiano do(a)s alunos permitindo-lhes maior autonomia para a realização de exercícios físicos fora do ambiente escolar, com base nas informações/vivências... (Resumo completo, clicar acesso eletrônico abaixo)
Keywords: Educação fisica; Exercícios físicos; Currículos